The Impact of Cognitive and Behavioral Symptoms on ALS Patients and Their Caregivers - Caga, Jashelle; Hsieh, Sharpley; Lillo, Patricia; Dudley, Kaitlin; Mioshi, Eneida (Frontiers in Neurology, 2019)
Previously thought to be a pure motor disease, amyotrophic lateral sclerosis (ALS) is now established as multisystem neurodegenerative disorder that lies on a continuum with frontotemporal dementia (FTD). Cognitive and behavioural symptoms primarily extend to executive function, personality, social conduct and emotion processing. The assessment and management of cognitive and behavioural symptoms is complicated as they must be differentiated from psychological responses to a terminal diagnosis and progressive physical impairment. This is made more difficult by the limited number of studies investigating how these symptoms specifically affect patients and caregivers well-being. The current review focuses on the impact of cognitive and behavioural symptoms on patient and caregiver well-being and their implications for future research and interventions in ALS. This is an important area of research that could form the basis for more tailored, and potentially more successful, non-pharmacological interventions to improve psychological well-being among patients with ALS and their caregivers.